LOGICO-SEMANTIC RELATIONS IN MENDEZ’ UTTERANCES IN ARGO - Dina Febriana (State University of Medan, 2018)
The study deals with the types of logico-semantic relations in Mendez’utterances in Argo. The objective of the study are to describe the types of logico semantic relations used in Mendez’ utterances and expalain how logico-semantic relations (unmarked and marked) used in Mendez’ utterances. This study was conducted by using descriptive qualitative. The data of the study were clause complexes found in Mendez’ utterances. There were 63 clause complexes found. Based on the analysis, it was found that only seven of ten types of logico-semantic relations were used in Mendez’ utterances. The logico-semantic relation type which dominantly occurs in Mendez’ utterances is unmarked enhancement (24 utterances, 38.09%). Then it’s followed unmarked extension (17 utterances, 26.98%), unmarked elaboration (11 utterances, 17.46%), marked enhancement (5 utterances,7.93%), marked locution ( 3 utterances, 4.76%), unmarked locution (2 utterances 3.17%), marked ectension (1 utterance, 1.58%). Meanwhile marked elaboration, unmarked idea and marked idea were not found in Mendez’utterances. Keywords : Logico-semantic relations, utterances